Peningkatan Keaktifan Belajar Pkn Melalui SrategiPembelajaran Two Stay Two Stray Dengan Media Teka-Teki Silang Pada Siswa Kelas V Di SDN Karangkebagusan Jepara Tahun Ajaran 2015/2016 - KHALIMATUS SA'DIYAH, UMMI (2016)
ABSTRACT Ummi Khalimatus Sa'diyah/A510120061. INCREASING ACTIVITY OF LEARNING CIVICS THROUGH LEARNING STRATEGY TWO STAY TWO STRAY WITH MEDIA CROSS WORD PUZZLE IN CLASS V IN SDN KARANGKEBAGUSAN JEPARA 2015/2016 ACADEMIC YEAR. Minithesis. The Faculty of Education, University of Muhammadiyah Surakarta. February, 2016. Learning that teachers do class V SDN Karangkebagusan still conventional in which teachers in delivering course material monotonous so that students are less active in the learning process. Learning like this make students feel bored and tired so active students in learning is very less. This study aims to improve the activity of learning civics in grade V SDN Karangkebagusan Jepara 2015/2016 school year through learning strategies Two Stay Two Stray media crossword puzzle. This research is a qualitative research and design research is a class act consisting of two cycles. Object of this research is the students' learning activeness. Technique data collecting by interview, observation and documentation. Data analysis techniques using data analysis interactive model. The results of the initial conditions of activity of students on average reaches 31%, then after the first cycle increased to 68% and after the second cycle increased to 89%. Increased activity of learning impact on increasing student learning outcomes which reached 80% of students scoring above the KKM (> 76) with an average grade 82.8, so it has reached an indicator of success. Based on the results of research conducted, it can be concluded that the activity of students of class V SDN Karangkebagusan Jepara Academic Year 2015/2016 after implementation strategy with two stay two stray media crossword puzzle can be increased. Keywords: activeness study, two stay two stray Strategy, Media Crosswords puzzle